2008
DOI: 10.1055/s-2008-1076603
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Assessment of the Brain Using Proton Magnetic Resonance Spectroscopy in a Growth-Restricted Human Fetus: Case Report

Abstract: Proton magnetic resonance spectroscopy (MRS) is a noninvasive method to assess concentrations of different metabolites in tissues, including the brain. We evaluated a fetus with growth restriction using Doppler ultrasound and proton MRS. Doppler assessment revealed absent end diastolic flow in the umbilical artery. Diastolic flow was increased in the middle cerebral artery. Proton MRS of the fetal brain showed lactate and a low N-acetylaspartate/choline index, metabolic markers of starvation/hypoxia. Proton MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…In particular, it has long been known that hypoxic injury during fetal development leads to significant structural and functional brain injuries in the offspring. [26][27][28][29][30][31][32][33] Selective vulnerability of striatal neurons has been described in children born after a pregnancy complicated by asphyxia. 54 Lower concentrations of N-acetylaspartate and creatine levels have also been found in the central nervous system tissue of fetuses affected by hypoxic conditions indicating neuronal loss or damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it has long been known that hypoxic injury during fetal development leads to significant structural and functional brain injuries in the offspring. [26][27][28][29][30][31][32][33] Selective vulnerability of striatal neurons has been described in children born after a pregnancy complicated by asphyxia. 54 Lower concentrations of N-acetylaspartate and creatine levels have also been found in the central nervous system tissue of fetuses affected by hypoxic conditions indicating neuronal loss or damage.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that ischemic-hypoxic conditions (IHCs) in pregnancy resulting from acute and chronic perinatal events have adverse consequences on fetal brain development that are not apparent at birth. [19][20][21][22][23][24][25][26][27] Although previous studies noted that in utero exposure to IHC is associated with fetal brain injury, [26][27][28][29][30][31][32][33][34][35] the role of IHCs in the development of ADHD is unexplored. Thus, we hypothesize that IHC is an independent risk factor for childhood ADHD.…”
mentioning
confidence: 99%
“…A preliminary study on a small number of term SGA fetuses reported that brain metabolic differences were detectable in the frontal lobe [25]. In addition, several spectroscopic studies have shown that fetuses diagnosed with early and severe IUGR presented specific metabolic changes, such as increased brain lactate [35,36] and lower NAA/Cr and NAA/Cho levels when compared to matched controls [15]. Interestingly, similar findings have been reported for congenital heart disease (CHD), a condition associated with poor brain blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…9 Our finding is in agreement with 2 previous studies that reported the presence of lactate by fetal brain MRS in IUGR fetuses. 17,26 Both studies, however, lack data about oxygenation and acid-base balance at delivery.…”
Section: Wwwajogorgmentioning
confidence: 99%
“…However, several authors have recently suggested that the potential evidence of cerebral lactate is an indicator of altered fetal cerebral metabolism in pathological conditions. [15][16][17] In this study, we sought to measure fetal cerebral lactate using 1 H MRS to evaluate whether it could represent a marker of brain damage in IUGR fetuses.…”
mentioning
confidence: 99%